Menumbuhkan Self-Love pada Remaja di MAN 2 Surakarta - Asifa Nuriah Marganingrum; Faqih Purnomosidi (ARDHI : Jurnal Pengabdian Dalam Negri, 2025)
Adolescence is a transition period from childhood to adulthood that is vulnerable to various psychological problems, such as searching for identity, social problems, academic pressure, and low self-confidence. Self-love or self-love is an important element in building mental health that is often overlooked, especially among adolescents. Based on the author's observations at MAN 2 Surakarta, it was found that students tend not to fully understand the concept of self-love, so they are vulnerable to social pressure, adakemik, and negative emotions. For this reason, this community service activity was carried out with the aim of instilling an understanding of the importance of self-love, recognizing oneself, and improving students' mental health. The implementation method used in this community service activity has three stages, namely: 1). Planning stage, 2). Implementation stage and 3). Evaluation stage. The results of this community service activity show that students begin to understand the importance of self-love as a basis for mental health. In conclusion, cultivating self-love is very important for adolescents to face psychological and social challenges. The application of this concept is expected to provide long-term benefits for students' mental and emotional well-being, as well as encourage their positive contributions in the social environment.